Characterisation of antimicrobial resistant Escherichia coli isolated from a dairy farm - Chapman, Sarah May Olivia (2016)
Antibiotic resistance is the greatest challenge facing modern medical practice with the prospect of completely resistant untreatable pathogens a potential outcome. One driver of this resistance is the widespread use of clinical antibiotics on livestock farms. This project investigated the antimicrobial resistance profiles of Escherichia coli isolated from a dairy farm, which had recently altered their antibiotic treatment regime. Strains of E. coli were selectively isolated from cow slurry and their antimicrobial resistance profiles compared to previously isolated strains from the same farm. No strains could be isolated using the antibiotic cefotaxime, which was previously successfully used for isolation. Three multidrug resistant E. coli strains, which showed a wider range of resistances than other strains were then sequenced to compare resistance genes presence with resistance phenotypes. The results of this study indicated that ESBL and multiple antibiotic resistant E. coli were significantly more difficult to isolate in 2014/15 compared to 2013, although multiple-drug resistant strains were still isolated. Phenotypic mercury chloride resistant strains were also more difficult to isolate in 2014/15 compared to 2013, however mercury chloride selective media were never used to isolate the strains. The carriage of mercury resistance genes correspondingly significantly decreased between the different strain groups. The antibiotic resistance genes were successfully shown within the three sequenced genomes residing on both mobile-genetic elements and chromosomally. The results of this project are consistent with the hypothesis that the reduced use of cephalosporins on this dairy farm positively affected the antibiotic resistance of the inherent E. coli population isolated using antibiotic selection.